Reservoir characteristics and genesis of the Lower Ordovician Tongzi Formation in central Sichuan Basin, China - Li Zhou; Hao Tang; Yading Li; Ruiqing Tao; Wei Yan; Tao Ma; Shuang Pan; Yi Du; Zhenbo Tan; Xuefei Yang (Frontiers in Earth Science, 2023)
Although the Ordovician petroleum exploration in the Sichuan Basin has been developed slowly for a long time, deepening the research of reservoir characteristics and genesis is still a robust way to accelerate it. This paper characterizes the Ordovician reservoirs in the central part of Sichuan Basin and analyzes their genesis based on cores, thin sections, well logs and drilling data. The results show the reservoirs concentrated in the Lower Ordovician Tongzi Formation, which consist mainly of sandy oolitic dolostones, bioclastic dolostones, fine crystalline dolostones, sandy dolomitized conglomerates, sandy dolostones and dolomite sandstone. The porosity types include interparticle pore, intraparticle pore, moldic pore, fracture and vug. Throats are mostly necked and flaky. The Tongzi Formation reservoirs mainly experienced three types of diageneses, including compaction, cementation and dissolution. The reservoir development was controlled by multiple factors of deposition, diagenesis and tectonics; the shoal facies is the basis, the penecontemporaneous dissolution and dolomitization are the main driving force, and the burial dissolution is the aid. The study can provide reference for deepening the Ordovician petroleum exploration and development in the Sichuan Basin.